A case study on the myth of emission from aliphatic amides. (19th December 2016) - Singh, Avinash Kumar; Das, Sreyashi; Datta, Anindya
Abstract: For several decades, aliphatic amidic compounds have been believed to be emissive. We report that this contention is incorrect and that the anomalous emission from amides originates in fluorescent impurities generated during their synthesis. In order to make this point, we have synthesized fluorescent compounds and have compared the absorption spectra with excitation spectra.